HUBUNGAN MOTIVASI IBU DENGAN KUNJUNGAN BALITA KE POSYANDU DI WILAYAH KERJA PUSKESMAS PERAWATAN PADANG GUCI KABUPATEN KAUR TAHUN 2024 - ARLENTI, Lety; Nurul Maulani; Rismayani; Fitri Yani Yustika (Program Studi D III Kebidanan Akademi Kesehatan Sapta Bakti Bengkulu, 2025)
The regularity of mothers in visiting the integrated health post and weighing their toddlers at the integrated health post will be very useful as monitoring the growth and development and nutritional status of toddlers. The percentage of coverage of toddler visits to the integrated health post in the Padang Guci Health Center working area is 70%. The purpose of this study was to determine the relationship between maternal motivation and toddler visits to the integrated health post in 2024. The research design used Cross Sectional. The study population was mothers who had toddlers totaling 439 people. The research sample was mothers who had toddlers aged 13-36 months as many as 93 people taken using the Accidental Sampling technique. Data collection was carried out by distributing questionnaires. Data analysis used the chi-square statistical test. The results of the study showed that out of 91 mothers of toddlers, almost half, 43 people (47.3%) had high motivation to visit toddlers to the integrated health post, out of 91 mothers who had toddlers, more than half, 57 people (62.6%) did not regularly visit toddlers to the integrated health post. The results of the bivariate analysis showed that there was a relationship between the motivation of mothers who have toddlers and toddler visits to the integrated health post in the working area of the Padang Guci Health Center, Kaur Regency in 2024 (p value = 0.030). It is hoped that health workers will increase health promotion about integrated health posts so that they can increase the motivation of mothers of toddlers to come to the integrated health post and make innovations in order to increase the interest of mothers of toddlers in visiting the integrated health post. Keywords : Motivation, Mother, Toddler, Posyandu